State, Modernity and Regional Society: Ayacucho, 1920-1940 - Gamarra, Jefrey (Universidad del Pacífico, 1992)
This article tries to answer two fundamental questions: how has Ayacuchan society been modernized; and, what social groups played a significant role in the process. The analysis centers on the ideologies of the 'mistis' land-owners and of the peasant natives during the twenties. The piece rounds off with the suggestion that there is more than coincidence of ideas between the Ayacuchan intellectuals of the first half of XXth Century and the leaders of Shining Path.